2000
DOI: 10.1046/j.1440-1681.2000.03212.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase I Inhibition By Nitric Oxide: Implications For Mediation Of The Hypercapnia‐Induced Vasodilator Response

Abstract: 1. At present, CO2 is considered to be the most important factor in regulating cerebral blood flow by modification of the interstitial fluid and extracellular pH, but the mechanism by which hypercapnia produces vasodilation is still controversial. In the present paper we investigated the effect of hypercapnia on carbonic anhydrase (CA) activity. We also studied the combined effects of CO2 with either indomethacin or an L-arginine analogue on CA activity. 2. Nine groups of 12 rabbits each were established. Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…For instance, the fast changes in pH that occur during hypocapnia and hypercapnia are important modulators of NO synthase. 32 Also, pharmacological manipulations of opiate receptors, 33 prostaglandins production, 34 and ATP-dependent K ϩ channel activation 35 were found to be involved in the modulation of CO 2 -NO cerebral vasomotor reactivity. The detailed discussion of this issue is beyond the scope of this article, and the final mechanism of this pathway remains to be explored.…”
Section: Lavi Et Al Nitric Oxide and Cerebral Blood Flowmentioning
confidence: 98%
“…For instance, the fast changes in pH that occur during hypocapnia and hypercapnia are important modulators of NO synthase. 32 Also, pharmacological manipulations of opiate receptors, 33 prostaglandins production, 34 and ATP-dependent K ϩ channel activation 35 were found to be involved in the modulation of CO 2 -NO cerebral vasomotor reactivity. The detailed discussion of this issue is beyond the scope of this article, and the final mechanism of this pathway remains to be explored.…”
Section: Lavi Et Al Nitric Oxide and Cerebral Blood Flowmentioning
confidence: 98%
“…This index was expressed as the sum of all lesions, as described in the literature. 20) b) Non-steroidal Antiinflammatory Drug (NSAID)-Induced Gastric Ulcers in Mice: In this model, 21) gastric ulcer was induced using piroxicam (30 mg/kg, s.c.) administered to mice. The crude MeOH extract or EAF from S. pseudoquina (250, 1000 mg/kg), cimetidine (100 mg/kg) or saline was administered orally 30 min before induction of the gastric ulcer.…”
Section: )mentioning
confidence: 99%
“…[24][25][26] It is known that efficient activators of CA possess a bulky aromatic/heterocyclic moiety and a primary/secondary amino group in their molecular structure. 26) Pauscas and Coltau 9) pointed out that the prostaglandin F2alpha activates the hydration activity of CA in vivo and in vitro, but the mo- ), in which the bromide ion binds to the zinc ion. lecular structure is very different from those of the common efficient activators of CA.…”
Section: Discussionmentioning
confidence: 99%
“…8) Puscas and Coltau have shown that prostaglandin F2alpha, enhances CA activity, resulting in an elevation of blood pressure. 9) Therefore, latanoprost is supposed to have some influence on CA activity in the eyes. CA is an enzyme found in many tissues of the body.…”
mentioning
confidence: 99%